Tax Avoidance dan Stabilitas Keuangan: Apakah Leverage Memperkuat atau Memperlemah Hubungan? - Febiani, Asila; Umyana, Ayu; Helmi, Syarif M. (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study was conducted to examine the relationship between tax avoidance practices and financial stability, by placing leverage as a moderating variable in property and real estate entities listed on the Indonesia Stock Exchange during the 2021-2023 period. The study used a quantitative methodology and applied a purposive sampling technique in selecting samples, resulting in 93 observation units. Tax avoidance was quantified using the Cash Effective Tax Rate (CETR), financial stability represented by cash flow volatility, and leverage operationalized by the Debt to Equity Ratio (DER). The analysis technique applied was Moderated Regression Analysis (MRA) accompanied by classical assumption testing. After conducting the analysis, the results showed that tax avoidance had a negative effect on financial stability, while leverage could increase financial stability if managed properly. In addition, leverage was unable to moderate the interaction between tax avoidance and financial stability. The company's financial stability is a major concern given the high capital requirements and operating cost pressures.
Keywords: Financial Stability; Leverage; Tax Avoidance